SEORANG LELAKI DENGAN MORBUS HANSEN TIPE BORDERLINE TUBERKULOID DISERTAI CACAT KUSTA TINGKAT 2 - Stefani Nurhadi (Universitas Ciputra Surabaya, 2023)
Leprosy is a chronic granulomatous disease caused by Mycobacterium leprae, which can cause significant disability in patients. Risk factors for leprosy include genetic susceptibility, environmental exposure, and social and economic factors. Diagnosis and classification of leprosy is based on clinical signs, skin examination, and histopathology. Defects arising in leprosy can result from bacilli infiltration of the skin and nerves, as well as from leprosy reactions in the form of acute neuritis. Prevention and treatment of hand and foot defects need to be done early and involve self-care by the patient. A case of MH type BT in a 29-year-old male with grade 2 leprosy was reported based on anamnesis, physical examination and supporting examination. The management given from the skin and genital department was MDT MB package I and vitamins B1 B6 B12 and the medical rehabilitation department consul was given intrinsic muscle stimulation of the hand, range of movement (ROM) exercises, movement, and functional hand. Leprosy treatment aims to break the chain of transmission, cure patients, and prevent disability. The leprosy eradication program involves treatment with a multi-drug treatment (MDT) regimen tailored to the type of disease. Prevention and treatment of disability in leprosy involves physical exercise, protection of hands and feet, and wound and skin care. People with leprosy also need to understand the importance of self-care and avoiding risk factors that can worsen the condition. Leprosy is a disease that can cause significant disability and impairment. Prevention and treatment of disability in leprosy plays an important role in improving the quality of life of patients. Leprosy eradication programs involving MDT treatment have been shown to be effective in reducing disease incidence. Self-care by sufferers through physical exercise, hand and foot protection, and wound and skin care can help prevent more severe disability. A holistic and comprehensive approach is expected to reduce the negative impact of leprosy on sufferers and society.